Clinical outcome and prevalence of osteoarthritis after isolated anterior cruciate ligament reconstruction using hamstring graft: follow-up after two and ten years - Struewer, Johannes (Springer-Verlag, 2012)
PURPOSE: The aim of this study was to evaluate patient-reported clinical outcome, instrumental stability and prevalence of radiological osteoarthritis (OA) based on a homogeneous patient sample after two years and on average ten years after isolated anterior cruciate ligament (ACL) reconstruction. METHODS: Primarily we performed ACL reconstruction using a four-strand semitendinosus tendon (ST) autograft in 112 patients. Two years after reconstruction 98 patients could be re-evaluated. Long-term clinical and functional follow-up assessment was then performed on 52 patients on average 10.2 years after operative treatment. Inclusion criteria consisted of an isolated ACL rupture, reconstruction with ST graft and no associated cartilage alterations and meniscal lesions. Clinical and functional follow-up assessment included the International Knee Documentation Committee (IKDC) score and the scores of Tegner and Lysholm. Instrumental stability testing was carried out with the KT1000™ arthrometer. The degree of degenerative changes and prevalence of OA was based on the Jäger-Wirth score. RESULTS: The mean long-term follow-up was 10.2 years (eight–13 years), and the mean age was 40.4 years (24–62 years). About 72 % of patients were graded A or B according to the IKDC score. Activity levels according to the scores of Tegner and Lysholm were 4.8 and 88.2 on long-term follow-up. Radiological assessment revealed degenerative changes in the sense of a grade I OA in 21.2 % of patients. Prevalence of a grade II OA was found in 53.8 % of patients. A grade III OA and a grade IV OA were found in 19.2 and 5.7 %. Correlation analysis showed significant relationships between the long-term stability and prevalence of OA (p < 0.05). CONCLUSIONS: Arthroscopic ACL reconstruction using four-strand ST autograft resulted in high patient satisfaction and good clinical results at two years and long-term follow-up. The prevalence of higher degree OA that developed in about 25 % of patients is significantly correlated with long-term knee joint stability.